Multimodal Ultrasonographic Manifestations of Small Cell Neuroendocrine Carcinoma of the Cervix: A Case Report - Lu Zhang; Yanzhao Wang; Bin Ma (Journal of Clinical Ultrasound, 2026)
ABSTRACT Small cell neuroendocrine carcinoma (SCNEC) is a rare high‐grade malignant tumor associated with high‐risk HPV infection. It is prone to early lymph node metastasis and distant metastasis. The main clinical manifestations are contact bleeding, pelvic masses, and abdominal pain. Conventional imaging examinations are not characteristic, but multimodal ultrasound can fully show the morphology, internal echoes, blood supply, tissue hardness, and other subtle characteristics of cervical neuroendocrine tumors.